Factors Contributing To Bom Change Management Issues- The Case Of Tis Department In Leadoff Engineering Technologies (M) Incorporated - Gani, Anisha Banu Dawood; Rosli, Rosdiana Mohd (2014)
Effectively managing a bills-of-material (BOM) change is critical in a manufacturing industry because of the possibility of a change to spread from one component to another. The Technical Information Service team (TIS) at Leadoff Engineering Technologies (LET) is entrusted to notify and obtain approval from all impacted stakeholders when an engineering change is initiated against a BOM. However, a recent complaint from an Internal Customer (IC) who failed to receive such notification from TIS, revealed a process gap in the way TIS manages this process.